World welfare is rising: Estimation using nonparametric bounds on welfare measure - Maxim L. Pinkovskiy (Federal Reserve Bank of New York, 2013)
I take a new approach to measuring world inequality and welfare over time by constructing robust bounds for these series instead of imposing parametric assumptions to compute point estimates. I derive sharp bounds on the Atkinson inequality index that are valid for any underlying distribution of income conditional on given fractile shares and the Gini coefficient. While the bounds are too wide to reject the hypothesis that world inequality may have risen, I show that world welfare rose unambiguously between 1970 and 2006. This conclusion is valid for alternative methods of dealing with countries and years with missing surveys, alternative survey harmonization procedures, and alternative GDP series, or if the inequality surveys used systematically underreport the income of the very rich or suffer from nonresponse bias.
Keywords: I31; C02; 330; world income distribution; inequality and welfare measures; nonparametric bounds